The implementation of warehouse management system (WMS) to improve warehouse performance in business to business (B2B) - Karishma, Shanmugamani; Fazeeda, Mohamad (Penerbit Universiti Malaysia Pahang, 2023)
As one of the key steps in the manufacturing supply chain, warehousing is in the position of controlling inventories. The success of realised goods movements can often be measured by how well warehouse activities are carried out. The goal of this study is to identify the problems with inventory management in warehouses and to install WMS to enhance inventory control in a warehouse setting. In industries such as manufacturing and other forms of production, efficient warehousing and management of inventory is essential. A systematic evaluation is used throughout the literature to investigate warehouse operational challenges and how they impact performance measures. As clients develop increasingly sophisticated and require precise, safe, and rapid information communication, this study develops and comprehends the usage of technological advances to support the business and incorporate trustworthiness, control, and flexibility into the daily operations of warehouses. The main goal of this study was to enhance the work management system of the organisation. The outcomes from this study offer a few helpful suggestions on applying WMS practises within the organisation.